Peningkatan Kompetensi Guru SD dalam Mendesain Local Instruction Theory untuk Mendukung Pembelajaran Inovatif pada Kurikulum Merdeka - Apriani, Ika Fitri; Saputra, Erwin Rahayu; Putri, Agnestasia Ramadhani; Insani, Andi Mutiara; Syaripah, Auliya (FKIP Universitas Sebelas Maret, 2024)
The aim of the service activity is to provide insight and increase the professionalism of teachers in Tasikmalaya City in designing Local Instructional Theory (LIT) for innovative learning in elementary schools. The innovative learning models offered are the Problem Based Learning (PBL) learning model, and Project Based Learning (PjBL). Overall, teachers were not yet familiar with the concept of LIT, but when the training was carried out, teachers became aware and interested in developing a Local Instruction Theory design. Teachers' ability to develop Local Instruction Theory in learning is still very low. There are several factors that cause this to happen. First, teachers do not yet understand LIT and innovative learning models in the independent curriculum. Second, there is still a lack of training in creating/compiling/designing LIT in the independent curriculum. The partners' problem solutions include providing training and providing assistance to elementary school teachers to design LIT for learning. This training activity was attended by 20 elementary school teachers at one of the elementary schools in Tasikmalaya City. After attending the training, the participants gave a positive response and felt the need to carry out the next training.